Unemployment in the European Union: a dynamic reappraisal - Marika Karanassou; Héctor Sala; Dennis J. Snower (Queen Mary University of London, Department of Economics, 2002)
This paper examines the movements in EU unemployment from two perspectives: a) the NRU/NAIRU perspective, in which unemployment movements are attributed largely to changes in the long-run equilibrium unemployment rate and (b) the chain-reaction perspective, in which unemployment movements are viewed as the outcome of the interplay between labor market shocks and prolonged lagged adjustment processes. We present an empirical analysis that distinguishes between unemployment movement arising from long-run equilibrium changes and those arising from lagged intertemporal adjustments. This analysis has far-reaching policy implications. Our analysis shows that the rise in the EU unemployment over the 1970s and first part of the 1980s was due largely to permanent shocks (especially the rise in the working-age population and the decline in capital formation), whereas the unemployment increase in the first part of the 1990s was due largely to temporary shocks (especially the fall in competiveness and the rise in real interest rates).
Keywords: J64; E37; E30; J60; J32; 330; Unemployment; natural rate; NAIRU; labor market shocks; employment; labor force participation; wage determination; intertemporal adjustments; Arbeitslosigkeit; Natürliche Arbeitslosigkeit; Schock; Erwerbspersonenpotenzial; EU-Staaten